Trends in prevalence of hip osteoarthritis over a 10-year period in Japan: The ROAD study 2005–2015. Issue 3 (September 2022) - Iidaka, Toshiko; Horii, Chiaki; Muraki, Shigeyuki; Oka, Hiroyuki; Kawaguchi, Hiroshi; Nakamura, Kozo; Akune, Toru; Tanaka, Sakae; Yoshimura, Noriko
Abstract: Objective: The trends in prevalence of hip osteoarthritis (OA) over a 10-year period among Japanese men and women were investigated using the data from the Research on Osteoarthritis/osteoporosis Against Disability study. Design: We analyzed the data of 2924 baseline survey participants (1026 men, 1898 women) aged 40–89 years (mean 70.7 years) residing in urban, mountainous, and coastal communities who were surveyed in 2005–2007. We compared these data with that of 2347 participants (726 men, 1621 women) aged 40–89 years (mean 69.2 years) from the fourth survey in 2015–2016. The fourth survey invited participants to attend follow-ups for baseline survey and recruited new participants. After scoring the radiographs using the Kellgren/Lawrence (K/L) grading system, hip OA was defined as a K/L score ≥2. Results: The prevalence of radiographic hip OA was 18.4% and 14.4% in the baseline survey, and 16.0% and 10.7% in the fourth survey among men and women, respectively. Among the participants aged 40–69 years, the prevalence of radiographic hip OA was significantly lower during the fourth survey than during the baseline survey. Whereas, among elderly men aged 70–79 years, radiographic hip OA was significantly less prevalent during the baseline survey than during the fourth survey. From the logistic regression analysis results, radiographic hip OA was significantly less prevalent during the fourth survey than during the baseline survey (odds ratio: 0.55, 95% confidence interval: 0.46–0.65). Conclusion: At a 10-year interval, the prevalence of radiographic hip OA shows an improving trend.